Quasimonochromatic beam of parametric X-ray radiation for control of heavy elements - Shchagin, A.V.; Sanin, V.M.; Sotnikov, V.V.; Voronko, V.A.; Yegorov, A.M. (Вопросы атомной науки и техники, 2005)
Possibility to use quasimonochromatic X-ray beam of parametric X-ray radiation (PXR) in the X-ray locator for control and location of heavy elements is considered. The locator should operate with a tunable quasimonochromatic polarized X-ray beam in the energy range up to about 130 keV to cover all atomic energies of heavy elements. The effect of PXR from relativistic electrons moving through a crystal will be used in the X-ray generator of a quasimonochromatic, polarized, tunable X-ray beam. Therefore, the locator is based on a linear electron accelerator that provides the electron beam with energy of about several tens of MeV. The response signal of characteristic K-lines of X-ray radiation from the object under inspection is registered by spectrometric X-ray detector. The locator is able to detect of heavy elements at a tentative distance up to about several meters for several minutes.